PRIMARY SCHOOLS’ ENROLMENT AND DROPOUT RATES IN LOW INCOME NEIGHBOURHOODS AND THEIR IMPLICATIONS FOR COMMUNITY DEVELOPMENT IN KASARANI SUB COUNTY, NAIROBI COUNTY, KENYA - Kamau, Stephen Kibandi (Advances in Social Sciences Research Journal, 2017)
ABSTRACT This study assessed primary school’s enrolment and dropout rates in poor neighbourhoods of Kasarani and their implications for community development. This neighbourhood is expanding and is rarely mentioned when or where other similar settlements are discussed. Motivation for this study was drawn from the fact that this area has many schools and the fact that, education is an important form of human capital that improves productivity, health and nutrition of the people and slows down the population growth. Education as a need for development transforms communities from poverty to self-reliance. It was carried out in this area because it remains undeveloped despite establishment of the many schools and industries as well as lack of documented studies pertaining to Kasarani area. This area was also selected as it is among the poorest neighbourhoods presented in the national poverty survey recently conducted by the government of Kenya. Objectives of this study were; to assess schools’ enrolment and dropout rates, to explore factors determining dropout rates in poor neighbourhoods; to examine implications of enrolment and dropout rates to community development, and; to examine measures embraced by community and roles of dropout youths towards community development. Social disorganization theory reinforced by status delinquency theory informed the study. This study adopted a descriptive research design capturing qualitative and quantitative data that was collected through interviews. From a population of 17,088, a sample size of 99 parents and 60 teachers was drawn. Data was analyzed using Statistical Package for Social Sciences software and presented through tables, graphs and charts in the form of frequencies, percentages and correlation. It established that there was increased enrolment trend, 51.8% for boys and 48.2% for girls and a notable increase in dropout at 55.1% before completing primary education where by dropout rate for boys was 24.3% and that for girls was 30.8%. Schools’ dropout was due to lack of school fees, negligence, poor retention, sexual abuse and insecurity. Increased enrolment led to increased literacy level, better sanitation and while dropout has resulted to drug abuse, unemployment and insecurity. Generally, community and youths are playing a pivotal role in enhancing development via expansion of community based centres, formation of self-help groups, community clean-ups and variety of businesses. This study concludes that there was high enrolment at entry level to primary schools but also high rate of dropout towards higher levels. This study recommends relevant stakeholders to seriously address education issues in the poor neighbourhoods as a pillar in sustainable community development.